Integrated Transcriptomic and Metabolomic Analysis Reveals the Molecular Mechanisms Involved in the Adaptations of Mandarin Fish (Siniperca chuatsi) to Compound Feed - Yunyun Yan; Yuan Zhang; Junjian Dong; Fubao Wang; Hetong Zhang; Fengying Gao; Xing Ye; Chengbin Wu; Chengfei Sun (Fishes, 2025)
Siniperca chuatsi is an important high-quality freshwater aquaculture species in China. In nature, it feeds exclusively on live food. In this study, domesticated juvenile S. chuatsi were divided into three groups and fed live food (group L), compound feed (group C), or a mixed diet (group M) for three months to investigate the molecular mechanisms underlying adaptation to compound feed. Histopathological examination revealed that compound feed consumption induced looser liver cell arrangement, hepatocyte morphological irregularities, and vacuolization. A total of 1033 and 1428 differentially expressed genes (DEGs), and 187 and 184 differential metabolites (DMs), were identified in the C vs. L and C vs. M groups, respectively. Transcriptomic analysis revealed that the significantly and commonly enriched metabolic pathways shared by both comparison groups were predominantly involved in amino acid, carbohydrate, and lipid metabolisms. Metabolomic analysis demonstrated that the significantly and commonly enriched metabolic pathways shared by both comparison groups were the arachidonic acid metabolism, linoleic acid metabolism, oxidative phosphorylation, and PPAR signalling pathways. Integrated omics analysis showed that the PPAR signalling pathway was the only significantly co-enriched pathway across both omics datasets. This study provides new insights into the molecular mechanisms of compound feed adaptation and provides theoretical support for selecting feed traits in S. chuatsi.